Media ownership and its role in shaping news: analysing Republika's 1999 and 2021 coverage in light of the 2024 Gaza genocide - Benni Setiawan; Pawito Pawito; Sri Hastjarjo; Eko Prasetyo Nugroho Saputro (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to examine the reporting of the Israeli aggression towards in the Indonesian newspaper Republika during the years 1999 and 2021, with a contextual reference to the 2024 Gaza genocide. The reports were selected through purposive sampling, focusing on direct coverage from both 1999 and 2021. Additionally, interviews were conducted with members of Republika's editorial team. Using Entmanï¿½s framing theory as well as Shoemaker and Reeseï¿½s Hierarchy of Influences model, the research identifies notable differences in news framing between the two periods. In 1999, the coverage in Republika largely emphasised political support from prominent figures, both in Indonesia and internationally, advocating for the defence of Palestine. In contrast, the 2021 coverage highlighted support from civil society, including athletes and celebrities. Differences are also evident across several levels of the Hierarchy of Influences model, with the media routine, organisational, and ideological levels being the most prominent. In 1999, Republikaï¿½s reporting on the Israeli-Palestinian conflict in the international section was relatively independent, focusing primarily on political issues. By 2021, however, the reporting followed a compartmentalised model, where one section complemented and connected with others. Despite the differences in time and ownership, Republika's stance on the Israeli-Palestinian conflict remained consistent. The newspaper continues to assert that the Palestinian people must be defended, a position shaped by its Muslim readership, who maintain a strong psychological connection with Palestinian Muslims.